2010
DOI: 10.1088/0022-3727/43/42/425202
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure gas breakdown in longitudinal combined electric fields

Abstract: This paper contains the complete experimental and analytical picture of gas breakdown in combined electric fields for arbitrary values of rf and dc fields. To obtain it, we continued the study of the discharge ignition modes in nitrogen with simultaneous application of dc and rf electric fields presented in Lisovskiy et al (2008 J. Phys. D: Appl. Phys. 41 125207). To this end, we studied the effect of rf voltage on dc discharge ignition. When we applied an rf voltage exceeding the one corresponding to the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…These parallelisms have been obtained from high γ values emitted by the surface‐dominated cold plasma with the bombardment or photon absorption. However, both this study and the existing studies do not mention the relationship between the increasing of γ ph and the low applied voltages of the breakdown evolutions at the higher values of pd . Therefore, for the electron emission from the different semiconductor materials we conclude that the lower applied voltages of the breakdown with the significant enhancement of γ i levels are remarkably achieved by the surface–ion interactions depending on the value of ϕ .…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…These parallelisms have been obtained from high γ values emitted by the surface‐dominated cold plasma with the bombardment or photon absorption. However, both this study and the existing studies do not mention the relationship between the increasing of γ ph and the low applied voltages of the breakdown evolutions at the higher values of pd . Therefore, for the electron emission from the different semiconductor materials we conclude that the lower applied voltages of the breakdown with the significant enhancement of γ i levels are remarkably achieved by the surface–ion interactions depending on the value of ϕ .…”
Section: Resultsmentioning
confidence: 72%
“…This is reasonable as, during the energy conversions from the cathodes, the g values of an InP cathode significantly exceed the g values obtained from GaAs and Si cathodes. For the levels of either g i or g ph , the behavior of the g levels indicates that there are similar directions with [6,[14][15][16]54] for the semiconductor and metal cathodes in the breakdown evolution at the reduced or enhanced values of E/N. In particular, these studies indicated the g ph levels at the reduced values of E/N and the g i levels at the enhanced values of E/N.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…turning points, in more details see later) have been addressed in several previous works. [8][9][10] Electrical breakdown and discharges in hydrogen have been subjects of intense research due to the wide usage of this gas in a various technological processes: thin-film deposition, etching, cleaning, etc. 11,12 The breakdown in hydrogen has been previously studied both for DC 1,13,14 and RF fields.…”
Section: Introductionmentioning
confidence: 99%